Sistem Pendukung Keputusan Penilaian Kinerja Ketua Program Studi Menerapkan Metode WASPAS dengan Pembobotan ROC - Nasution, Mhd Bobbi Kurniawan; Kusmanto, Kusmanto; Karim, Abdul; Esabella, Shinta (Forum Kerjasama Pendidikan Tinggi, 2022)
The head of the study program is a figure who plays an important role in the progress of each study program at a university. The head of the study program has a role in the decision-making process and in carrying out managerial policies. In addition, the head of the study program is also a person who is able to ensure the creation of a conducive atmosphere in the service process to students and also the scope of work in the study program. Therefore, awarding the head of the study program based on the performance shown is a form of appreciation for the performance given by the head of the study program. The process of evaluating the performance of the head of the study program is not only an assessment of the academic field but also an assessment of the managerial. In the process of evaluating the performance of the head of the study program, a computerized tool is needed or commonly called a Decision Support System. The decision support system also has several settlement methods that are used as a reference, one of the methods that can be used is the WASPAS method. In addition to the methods used to support decisions, there are also methods that can be used for weighting each assessment criteria such as the ROC method. In this research, we will use the ROC weighting method on the assessment criteria and the process of evaluating the performance of the head of the study program using the WASPAS method. The results achieved in the research are to obtain an objective and accountable process of evaluating the performance of the study program leader. In the research that has been carried out, it is found that the Head of the Study Program who gets the reward is the Head of the Study Program with alternative A2 and the preferred value is 0.958